Avaluation of the potential of natural vegetable products in mosquito morality Aedes aegypti/Avaliação do potencial de produtos naturais de origem vegetal na mortalidade da larva do mosquito Aedes aegypti - Keyth Daiann Felix Palmeira; Ana Paula Pereira de Oliveira Silva; José Atalvanio da Silva; Claudimary Bispo dos Santos (Universidade Estadual de Alagoas, 2020)
Arboviruses are diseases caused by viruses, which are transmitted by arthropods. Hematophagous arthropods are vectors, the most common being the Aedes aegyptimosquito. The objective of this work was to evaluate the larvicidal potential of natural products of plant origin on Aedes aegyptilarvae. The work was carried out at the Chemistry Laboratory of the State University of Alagoas, on Campus I. Fresh extractswere produced containing 40g of the following materials: boldo-do-chile, mint, aloe vera, cloves, cinnamon, garlic, ginger and capim-santo, added to 150ml of distilled water in each extract for 15 days. The suspension was filtered through a sieve, obtaining the extracts that were used in the tests. The larvae of Aedes aegypti used in the experiments came from the municipality of Arapiraca -AL, which were taken to the chemistry laboratory, for proper identification and kept at room temperature.The pre-test was done in duplicate, the larvae were inserted with the aid of a pipette, two larvae per repetition. 10 mL were added to each pot mineral water and 10 mL of the aqueous and capped extract were added to each pot andkept at room temperature. The larvae wuere analyzed at 24 h, 48 h and 72 h. Its purpose was to know the power of herbs in larval mortality and to select the ones that had the best performance. The plant materials that had the best performance in larval mortality were cloves, cinnamon and garlic. The aqueous extracts were prepared for the test, this time, 7 repetitions were performed, with 2 larvae in each pot. The analyzes ran in 1 h, for 24 h, until larval mortality. The test revealed the lethal potential in the extracts, Clove obtained 100% after two hours, Garlic 92,85% after two hours and Cinnamon 42,85% after 10 hours. This fact corroborates the observations found in similar studies. In view of the results, it was found that the aqueous extracts of cloves and garlic had a fasteraction on the mortality of Aedes aegyptimosquito larvae than cinnamon. Thus, the aqueous extracts of garlic, cloves and cinnamon presented as a natural alternative to combat larvae of the mosquito Aedes aegypti. The results were considered promissing, asit is na alternative where the population can have access in na economical and simple way.